Sustainable value creation? Entrepreneurial orientations in the football industry. Issue 1 (17th December 2020) - Bull, Mike; Whittam, Geoff
Abstract : Purpose: In this paper the authors investigate precarious value creation in English football clubs. They examine strategic, economic, cultural and social capital to analyse the orientations of legal owners of football clubs (entrepreneurs) and the implications for moral owners (the fans). Their research question is not if entrepreneurs create value – but whether the value created is productive or destructive. Design/methodology/approach: The research design is a case study of the professional football industry, specifically 44 football clubs in the top two professional divisions in England, namely the English Premier League and the English Football League Championship. The authors' methodology is secondary textual data. Their approach is to examine official club statements, triangulated with regional and national press reports, fan accounts and narratives from published artefacts; fan blogs and websites. Findings: The "opening up" of the professional football industry in England to market forces in 1983 has subsequently attracted entrepreneurs that use football clubs as artefacts to pursue other business interests. Over-grazing on strategic and economic capital at the expense and exploitation of social and cultural capital exists. As entrepreneurial opportunities to exploit a football club's assets becomes more apparent, the unique relationship between club and fan is being strained. The authors observe detachment, disenchantment and protest. Research limitations/implications: The data sought for this study design was necessarily in the public domain and therefore drawn from secondary sources. The scope was English football and the top two divisions, thus the findings are context specific to that region and level. Practical implications: For policy, the authors call for a new government inquiry into football ownership in English football, re-examining heritage, purpose and value creation. Social implications: Football fans are the majority stakeholder in the football industry but are under-represented in English football because of the private ownership of football clubs. Fans are, however, a barometer for how their owners are acting as custodians of their clubs and if the value created by entrepreneurs is productive or exploitative. Originality/value: This paper has value in drawing attention to this unique and ignored industry from an entrepreneurship perspective, provoking a call for further research to explore this phenomenon. Sustainable value creation may be a useful framework for further research in this and other industries.